Selection of New Field Pea Varieties for the Organic and Conventional Farming Systems in the Nemoral Climatic Zone - Žydrė Kadžiulienė; Monika Toleikienė; Kristyna Razbadauskienė; Lina Šarūnaitė; Irena Deveikytė; Skaidrė Supronienė; Roma Semaškienė; Aušra Arlauskienė (Agriculture)
Field pea (Pisum sativum L.) is one of the most important grain legumes in European agriculture, having many benefits for agro-ecosystems and also one of the lowest carbon footprints of any crop. However, this crop has many more drawbacks when grown organically as opposed to conventionally. Therefore, our study aims to investigate the performance of newly bred field pea varieties and to test their differences of adaptivity to organic and conventional farming systems. Our study evaluated productivity, as well as the biological and nutritional parameters of the following four new field pea varieties: Lina DS, Egle DS, Ieva DS and Jura DS, all cultivated in the Nemoral climatic zone, where field peas are widely produced. The performance was compared with the long-term standard field pea variety Ingrid. Our study showed that all investigated new varieties had higher productivity compared to the long-term standard Ingrid. The organic cropping system limited the grain yield of field pea, and different varieties tended to respond differently to this type of crop management. Therefore, different varieties should be selected and suggested for organic and conventional cropping systems. Furthermore, with various different responses to the precipitation level, different varieties could be suggested for farming in different regions. The nutritional value (content of proteins and amino acids) also responded significantly to the management system and the selection of field pea variety. Newly bred variety Egle DS demonstrated the highest grain yields, and the highest content of proteins and essential amino acids in the seeds of field pea grown in an organic farming system. Egle DS accumulated 30 percent higher content of arginine compared to the standard variety.